PENENTUAN PREDIKSI JUMLAH GERHANA MATAHARI DENGAN ARGUMEN LINTANG BULAN DAN ARITMATIKA - Izzuddin, Ahmad; Hidayat, Ehsan (ELFALAKY: Jurnal Ilmu Falak, 2022)
Variation in the number of solar eclipses is one of the number phenomena that occurs every year. Territorially, eclipses can occur and be observed once or twice and globally, solar eclipses can occur in quantities of 2 until 5. There are several literatures that say the minimum-maximum number is different from the data above. With a statistical approach, this paper examines one of the important components of the initial eclipse prediction algorithm, which is the value of the argument of moon’s latitude symbolized by large F and through arithmetic used to find a pattern of variations in a number. There are two interesting findings, the first argument of moon’s latitude value has a regular number pattern on each lunation, which is increased by 30,6705. Second, if in general people have to predict eclipses every month, then this study suffices data from the beginning of the new moon in a year, to be able to find out the eclipse in the months after or before.